Sustainability Balanced Scorecard and Management Communication in Evaluating A Company’s Performance - Sri Werastuti, Desak Nyoman (Jurnal Ilmiah Akuntansi dan Bisnis; Vol 16 No 1 (2021)DO - 10.24843/JIAB.2021.v16.i01.p03, 2020)
This study examines the effectiveness of Sustainability Balance Scorecard (SBSC) and management communication in evaluating company performance. Furthermore, to determine the role of the use of high management communication and the use of the sustainability balanced scorecard in increasing the manager's bonus award decisions. Laboratory experiment was carried out on 94 students of accounting, Faculty of Economics, Ganesha University of Education. Results show that the use of the SBSC influences in evaluating performance. In addition, environmental perspective and the high level of management communication have a significant influence on the decision of managers on bonus allocation. Keywords:       environmental perspective, sustainability balanced scorecard, management communication, performance evaluation.